Pearlite Rail

The pearlite rail addresses wear resistance and ductility issues by optimizing nitride particle distribution and chemical composition, enhancing durability and service life in heavy-duty railway applications.

JP7620259B1Active Publication Date: 2025-01-23NIPPON STEEL CORPORATION
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024555965
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-06-14
Publication Date
2025-01-23
Estimated Expiration
2044-06-14

AI Technical Summary

Technical Problem

Heavy-duty railways face reduced service life due to insufficient wear resistance in the Gauge Corner section and head side of rails, particularly in sharp curves, necessitating a rail with enhanced wear resistance and ductility.

Method used

A pearlite rail composition with controlled nitride particle distribution, where nitride particles in the ferrite phase are fine and dense, and those at the cementite interface are minimized in size and number, combined with specific chemical elements and manufacturing processes to achieve optimal hardness and wear resistance.

Benefits of technology

The pearlite rail exhibits improved wear resistance and ductility, maintaining structural integrity under heavy loads and extending service life by minimizing nitride particle-induced strain accumulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620259000009
    Figure 0007620259000009
  • Figure 0007620259000010
    Figure 0007620259000010
  • Figure 0007620259000011
    Figure 0007620259000011
Patent Text Reader

Abstract

A pearlite rail according to an embodiment of the present disclosure contains, by mass%, C: 0.65 to 1.20%, Si: 0.05 to 2.00%, Mn: 0.05 to 2.00%, Cr: 0.02 to 2.00%, N: 0.0020 to 0.0200%, V: 0.010 to 0.100%, Nb: 0% or more and less than 0.005%, Ti: 0% or more and less than 0.005%, Mo: 0 to 0.100%, and the balance being Fe and impurities. The structure in the range from the outer surface of the head to a depth of 25 mm contains a pearlite structure by area ratio of 95% or more, the hardness at a position 25 mm deep from the surface of the top of the head is at least HV350, and the number density per unit interface area of ​​V-containing nitride particles with a particle size of 4 nm or more that are present on the cementite interface of the pearlite structure at a position 25 mm deep from the surface of the top of the head is 1.0 x 10 10 pieces cm -2 is less than.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a pearlitic rail intended to simultaneously improve the wear resistance and ductility of the head of a rail used in heavy-duty railways. [Background technology]

[0002] Heavy-duty railways overseas are promoting the high concentration of freight in order to improve the efficiency of railway transport. In particular, in rails with sharp curves, the wear resistance of the GC (Gauge Corner) section and head side sections cannot be sufficiently ensured. This has led to a problem of reduced rail life due to wear. In this context, there is a demand for the development of rails with wear resistance equal to or greater than that of currently used high-strength rails containing eutectoid carbon steel.

[0003] It is generally known that the higher the hardness of a rail, the better its wear resistance. However, in reality, as described in Non-Patent Document 1, it has been reported that wear resistance is improved by work-hardening the surface layer during use, increasing its hardness. In addition, as described in Non-Patent Document 2, it has been shown that pearlite steel, which has excellent work-hardening characteristics, is more excellent in wear resistance than martensitic steel or bainitic steel, which simply have high initial hardness. However, it has not been shown what kind of microstructural structure of pearlite steel has excellent wear resistance, and there has been insufficient guidance for rail manufacturing.

[0004] Patent Document 1 describes that adding a certain amount of a carbonitride-forming element such as Ti, V, Nb, or Mo forms these carbonitride precipitate particles in the austenite phase, suppresses the grain growth of austenite during hot rolling, and forms fine grains, thereby refining the block size after pearlite transformation and improving ductility.

[0005] Furthermore, Patent Document 2 discloses a method of improving wear resistance by adding W, V, Nb, etc. to precipitate carbonitrides in the ferrite phase after pearlite transformation and strengthen the ferrite phase. These two documents suggest that adding the same type of element improves different properties of rails.

[0006] While these mainly use carbides as precipitates in pearlite, Patent Document 3 describes improving fatigue damage resistance and wear resistance by precipitating fine particles of nitride in ferrite. Patent Document 4 describes improving fatigue damage resistance and delayed fracture resistance by precipitating fine particles of nitride in ferrite. These documents specify the particle size, number density, and component composition of the nitride particles precipitated in ferrite.

[0007] Patent Document 5 describes a steel rail containing, by mass%, C: 0.65-1.20%, Si: 0.05-2.00%, Mn: 0.05-2.00%, Cr: 0.02-2.00%, and further containing at least 0.005% or more of two or more of V, Nb, Ti, and Mo, and containing V+Nb+Ti+Mo: 0.02-0.20%, with the balance being Fe and unavoidable impurities, and having a head hardness of at least 340 Hv, in which the number density of carbonitriding precipitate particles of 10 nm or less in the ferrite phase is 5×10 15 cm -3 A pearlite rail is disclosed, characterized in that:

[0008] Patent Document 6 discloses a method for producing a high-toughness rail in which, when steel containing 0.60 to 1.20% C is rolled into a rail, continuous finish rolling is performed in the finish rolling, with rolling at a temperature of 850 to 1000°C with a cross-sectional area reduction rate of 5 to 30% per pass in two or more passes with an interval of 8 seconds or less between rolling passes, followed by cooling to 800 to 950°C at a cooling rate of 0.5 to 50°C / s, and then natural cooling or accelerated cooling. [Prior art documents] [Non-patent literature]

[0009] [Non-Patent Document 1] Ueda, M. et al., "Effect of Hardness and Carbon Content on Rolling Contact Wear of Pearlitic Steels", Iron and Steel, Japan, Iron and Steel Institute of Japan, 2001, Vol. 87, No. 4, P190-197 [Non-Patent Document 2] Ueda, M. et al., "Effect of Metal Microstructure on Rolling Contact Wear of High Carbon Steels," Iron and Steel, Japan, Iron and Steel Institute of Japan, 2004, Vol. 90, No. 12, P1023-1030 [Patent documents]

[0010] [Patent Document 1] JP 2010-1500 A [Patent Document 2] JP 2007-51348 A [Patent Document 3] International Publication No. 2020 / 054339 [Patent Document 4] JP 2020-70495 A [Patent Document 5] JP 2015-158006 A [Patent Document 6] JP 2001-234238 A Summary of the Invention [Problem to be solved by the invention]

[0011] In view of this background, there has been a demand for a pearlitic rail for use in heavy-duty railways, which has excellent head hardness, wear resistance, and ductility, and a method for manufacturing the same. The use of nitride particles, which has been practiced in recent years, is excellent in terms of removing unnecessary solid-solute N that has remained as an impurity until now, and in terms of rail hardening. However, knowledge regarding the position at which nitride particles are precipitated in pearlite has not been sufficient. The present disclosure has been devised in view of the above-mentioned problems, and its purpose is to simultaneously improve the wear resistance and ductility of the head portion required for rails of heavy-duty railways. [Means for solving the problem]

[0012] The present inventors have conducted detailed structural studies on the surface hardness and internal hardness of pearlite rails, as well as the rolling wear surface. As a result, the present inventors have found that the wear test narrows the spacing of the pearlite lamellae in the contact surface region (refining of pearlite lamellae), and the pearlite lamellae are further microcrystallized, resulting in a significant increase in the hardness of the surface region, and the greater the increase in hardness, the better the wear resistance. In the hardness increase due to the thinning of lamellae and microcrystallization, the lamellar ferrite (ferrite phase) in the pearlite is soft and highly ductile, making plastic deformation easier, and the pearlite structure consisting of lamellar cementite and lamellar ferrite is easily thinned and refined. This time, it was found that if there is a factor that inhibits this, it will cause a decrease in wear resistance and the occurrence of fatigue damage.

[0013] In pearlite rails that utilize nitride precipitate particles and clusters, the precipitation positions of nitride particles in the lamella of pearlite structure 1 are mainly as shown in Figure 1. (1) The center of lamellar ferrite 12 and (2) Cementite 11 / ferrite 12 interface (hereafter referred to as cementite interface 13) It was found that the nitride particles 22 distributed in the center of the ferrite 12 contribute to hardening the pearlite structure 1 through the hardening of the ferrite 12. On the other hand, the nitride particles 21 precipitated at the cementite interface 13 hardly contribute to hardening. In addition, since the nitride particles 21 precipitated at the cementite interface 13 are relatively large, they do not undergo plastic deformation or decompose even when the rail is repeatedly worn. Therefore, it was found that the nitride particles 21 precipitated at the cementite interface 13 cause a decrease in the wear resistance and ductility of the rail. Therefore, it was found that in a pearlite rail using nitrides, it is necessary to reduce the number of nitride particles 21 on the cementite interface 13 and to reduce their size.

[0014] On the other hand, the nitride particles 22 precipitated within the ferrite 12, rather than on the cementite interface 13, strengthen the ferrite 12, thereby increasing the hardness of the rail itself. In particular, when the nitride particles 22 precipitated within the ferrite 12 are fine and distributed at a high number density, they can be utilized for hardening without reducing the wear resistance or ductility.

[0015] The present disclosure has been made based on the above-mentioned new findings in order to solve the above-mentioned problems, and the gist of the disclosure is as follows.

[0016] (1) A pearlite rail according to an embodiment of the present disclosure comprises, by mass%, C: 0.65 to 1.20%, Si: 0.05 to 2.00%, Mn: 0.05 to 2.00%, Cr: 0.02 to 2.00%, N: 0.0020 to 0.0200%, V: 0.010 to 0.100%, Nb: 0% or more and less than 0.005%, Ti: 0% or more and less than 0.005%, Mo: 0 to 0.100%, B: 0 to 0.0050%, Co: 0 to 1.00%, Ni: 0 to 1.00%, Mg: 0 to 0.0200%, Ca: 0 to 0.0200%, Cu: 0 to 1.00%, REM: 0 to 0.0500%, and Zr: 0. The head has a structure ranging from the outer surface of the head to a depth of 25 mm, and contains a pearlite structure with an area ratio of 95% or more. The hardness at a position 25 mm deep from the surface of the head is at least HV350. The number density per unit interface area of ​​V-containing nitride particles having a particle size of 4 nm or more and present on the cementite interface of the pearlite structure at the position 25 mm deep from the surface of the head is 1.0 × 10 10 pieces cm -2 is less than. (2) In the pearlitic rail described in the above (1), preferably, V-containing nitride particles having a particle size of 0.5 to 4 nm and separated from the cementite interface in the ferrite of the pearlitic structure have a number density per unit volume of 4.0 × 10 16 ~4.0×10 17 pieces cm -3 It exists in the range. (3) Preferably, the pearlitic rail described in (1) or (2) above further contains, by mass%, one or more selected from the group consisting of B: 0.0001-0.0050%, Co: 0.01-1.00%, Ni: 0.01-1.00%, Mg: 0.0005-0.0200%, Ca: 0.0005-0.0200%, Cu: more than 0% and not more than 1.00%, REM: 0.0005-0.0500%, Zr: 0.0001-0.0200%, Al: more than 0% and not more than 1.000%. Effect of the Invention

[0017] According to the present disclosure, it is possible to provide a steel rail having a pearlitic structure with excellent wear resistance and ductility. That is, the present disclosure presents a method for producing a rail having improved wear resistance and ductility by suppressing the decrease in wear resistance caused by nitride particles precipitated at the cementite / ferrite interface. [Brief description of the drawings]

[0018] [Figure 1] FIG. 2 is a schematic diagram showing the distribution of precipitate particles in a rail pearlite structure. [Diagram 2] FIG. 1 is a diagram showing the relationship between the number density of nitride particles on a cementite interface and the amount of wear. [Diagram 3] FIG. 2 is a diagram showing the designations of the rail heads. [Figure 4A] This is an example of a 3D element map of Fe (iron) in a V-added rail. [Figure 4B] This is an example of a 3D elemental map of C (carbon) in a V-doped rail. [Figure 4C] An example of a 3D elemental map of V (vanadium) detected by V2+ ions in a V-doped rail. [Figure 4D] An example of a 3D elemental map of V (vanadium) detected by VN2+ ions in a V-doped rail. [Figure 5A] FIG. 4C is an example of a 3D elemental map of C, enlarged from the boxed region X in FIG. 4D. [Figure 5B]FIG. 4D is an example of a 3D elemental map of V, enlarged from the boxed region X in FIG. 4D. [Figure 5C] FIG. 4E is an example of a 3D elemental map of Cr, enlarging the boxed region X in FIG. 4D. [Figure 5D] FIG. 4E is an example of a 3D elemental map of Mn, enlarging the boxed region X in FIG. 4D. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The inventors conducted rolling wear tests on pearlitic steels with various compositions and manufacturing methods to investigate what strongly affects the wear resistance of pearlitic rails that utilize nitrides. The inventors then observed the structures before and after the wear tests using a transmission electron microscope (TEM) to investigate the relationship between the changes in structure and wear resistance properties in detail. Furthermore, the inventors investigated the location, number density, and composition of fine nitride particles (including even finer clusters) in pearlitic steels using a three-dimensional atom probe to investigate the relationship with the wear resistance properties of pearlitic rails.

[0020] FIG. 1 is a diagram showing a schematic diagram of the distribution state of nitride precipitates and clusters in the pearlite structure 1 of a rail. In general, pearlite lamellae are composed of lamellar ferrite 12 with a width of 80 to 200 nm and lamellar cementite 11 with a width of 10 to 20 nm. The means for increasing the hardness of a rail with the same C content are either to reduce the pearlite lamellar spacing (fine grain strengthening) or to increase the hardness of ferrite 12. Although a method of increasing the hardness of cementite 11 is also conceivable, the hardness of cementite 11 is already quite high, and it is practically difficult to intentionally increase this hardness further. In addition, if the hardness of ferrite 12 is simply increased significantly, the rail surface becomes difficult to plastically deform during use, and the increase in hardness of the wear surface due to the thinning and refinement of pearlite lamellae does not occur. On the other hand, when hardening is achieved with very fine nitride particles, plastic deformation is not completely suppressed, and it has been found that the fine nitride particles decompose during wear and do not become the starting points for cracks or voids, but form solid solution atoms or dipoles of N with V or Cr, etc., thereby contributing to hardness and wear resistance.

[0021] This detailed structural observation revealed that the nitride particles are mainly precipitated at two locations: the cementite interface 13 (i.e., the interface between the lamellar cementite 11 and the lamellar ferrite 12) and the central part of the lamellar ferrite 12, which is distant from the cementite interface 13. Here, the central part of the lamellar ferrite 12 refers to a region 5 nm or more away from the cementite interface 13. Of the cementite interface 13 and the central part of the ferrite 12, the nitride particles 22 distributed in the central part of the ferrite 12 contribute to hardening, but the nitride particles 21 precipitated on the cementite interface 13 are considered not to contribute to hardening. In addition, since the nitride particles with a slightly larger size do not deform or decompose due to wear, strain is concentrated around the nitride particles, and the nitride particles become the starting points of voids and cracks, which are considered to cause a decrease in wear resistance, ductility, etc. Therefore, it is necessary to make the nitride particles 21 on the cementite interface 13 smaller, and to reduce the number density of the larger ones. In addition, it was believed that by precipitating the nitride particles 22 in the ferrite 12 finely and in a high number density, they could contribute to hardening without reducing ductility or wear resistance.

[0022] By devising chemical components and heat treatment, the inventors have produced pearlite rails in which the hardness (strength) of the initial pearlite is within a certain range, but the size and distribution of nitride particles in the pearlite are different. The relationship between the nitride particle distribution and wear resistance was investigated by analyzing the structure and performing wear tests on these pearlite rails. A Nishihara wear tester was used to quantitatively evaluate wear resistance. In the wear tests, the wear amount was compared after 700,000 repetitions at a contact pressure of 640 MPa and a sliding ratio of 20%.

[0023] Figure 2 shows (1) the relationship between the number density per unit interface area of ​​nitride particles of 4 nm or more observed on the cementite interface and the wear volume for each pearlite rail sample, and (2) the relationship between the number density per unit interface area of ​​nitride particles of 0.5 nm or more and less than 4 nm on the cementite interface and the wear volume for a rail sample that does not contain nitride particles of 4 nm or more. Here, rail samples with a Vickers hardness of 380 to 400 Hv at a depth of 25 mm from the surface were used. The particle size and number density of the precipitated particles were investigated using a three-dimensional atom probe.

[0024] According to the survey results shown in Fig. 2, the number density of nitride particles with diameters of 4 nm or more on the cementite interface is 1.0 × 10 10 pieces cm -2 It can be seen that the wear amount increases when the number density of nitride particles with a diameter of 4 nm or more on the cementite interface is 1.0 × 10 10 pieces cm -2 If the diameter of the nitride particles is less than 0.5 nm, the wear amount of the rail is not significantly different from that of a rail that does not contain any precipitates. Also, if nitride particles with diameters of 0.5 nm to 4 nm are plotted on this figure, it can be seen that there is no correlation with the wear amount. In other words, even if relatively small nitride particles precipitate on the cementite interface, their effect on the reduction in wear resistance is small.

[0025] If relatively large nitride particles are present on the cementite interface, not only do they not contribute to improving rail hardness, but also strain accumulates at the particle position of the cementite interface during wear tests, forming voids and cracks, which can cause destruction. Therefore, the presence of many relatively large nitride particles on the cementite interface is interpreted as an increase in the amount of wear. However, if the nitride particles are very fine, they will decompose during wear. Therefore, strain does not accumulate around the fine nitride particles, and this does not lead to a decrease in wear resistance.

[0026] From the above basic experiments, in order to improve the wear resistance of pearlitic rail steel that utilizes nitride particles for hardening, it is desirable to make the size of the nitride particles on the cementite interface very small, or to reduce the number density of large nitride particles on the cementite interface.

[0027] On the other hand, for nitride precipitation in pearlite, the cementite interface is the preferred nucleation site. For this reason, nitride precipitation at the cementite interface is more likely to occur than nitride precipitation within ferrite grains, which acts on hardening. Therefore, when nitride particles are precipitated within ferrite grains, it is difficult to completely suppress precipitation at the cementite interface. It is necessary to reduce the precipitation of nitride particles at the cementite interface by narrowing the range of manufacturing conditions for the ingredients and thermomechanical treatment.

[0028] The reasons for the limited range of the pearlitic rail according to this embodiment will be described below. The head of a pearlite rail is usually worn during use due to contact with the wheels. Therefore, from the viewpoint of extending the life of the pearlite rail, it is required that the pearlite rail has properties suitable for railway rails not only on the surface of the head but also at a depth of 25 mm from the head. In addition, the pearlite lamellae are more likely to be finer and harder on the surface of the pearlite rail than at a depth of 25 mm, so that wear resistance is easily ensured. A pearlite rail having suitable properties at a depth of 25 mm from the surface of the head naturally has suitable properties on the surface of the head. In consideration of the above circumstances, in the pearlite rail according to this embodiment, the particle size, number density, and hardness of the V-containing nitride are limited at a depth of 25 mm from the surface of the head. In addition, in the pearlite rail according to this embodiment, the amount of pearlite structure is limited to a depth of 25 mm from the surface of the outer casing of the head.

[0029] (V-containing nitrides) In the pearlite rail according to the present embodiment, the nitride particles containing V are specified. The nitride particles containing V are nitride particles with a V content of 1 atomic % or more. Generally, a nitride is a crystal phase composed of N and a metal element, and there are nitrides composed of one type of metal element such as VN, TiN, NbN, and CrN, and nitrides composed of multiple types of metal elements such as (V,Cr)N and (Ti,V)N. (V,Cr)N is a nitride in which V and Cr are mixed, and (Ti,V)N is a nitride in which Ti and V are mixed. The elements in parentheses are listed in descending order of the number of atoms. In general, fine ones that are compatible with the ferrite matrix have a NaCl type crystal structure. On the other hand, carbides are a crystal phase in which N is replaced with C, and may contain a small amount of N as carbonitride. The nitride particles described in this disclosure do not contain C. Not containing means that the C solid solution concentration is equal to or less than the concentration in the matrix (ferrite phase) in which the nitride particles exist. Nitrides can precipitate finer than carbides and are often called clusters. In this specification, such fine particles (0.5 to 4 nm) are also referred to as nitride particles.

[0030] (1) Grain size and number density of V-containing nitrides on the cementite interface in the pearlite structure at a depth of 25 mm from the head outer surface The number density of nitride particles on the cementite interface has almost no effect on the strength of the ferrite phase. This is because the nitride particles on the cementite interface do not hinder the movement of dislocations in the ferrite. However, the nitride particles on the cementite interface do affect the wear resistance. In particular, the wear resistance decreased as the number density of nitride particles on the cementite interface increased beyond a certain size. This is because large nitride particles do not deform or decompose, and so strain accumulates around them, becoming the source of voids and cracks.

[0031] Therefore, in order to maintain sufficient wear resistance, the number density per unit interface area of ​​V-containing nitride particles with a grain size of 4 nm or more present on the cementite interface must be less than 1.0 × 10 10 pieces cm -2The nitride particles on the cementite interface have almost no effect on the deterioration of wear resistance when they are small in size, so there is no particular limitation on the number density as long as the nitride particles are smaller than 4 nm.

[0032] (2) Grain size and number density of V-containing nitrides in ferrite in the pearlite structure at a depth of 25 mm from the head outer surface In the ferrite, V-containing nitride particles with a particle size of 0.5 to 4 nm separated from the cementite interface are present at a number density of 4.0 × 10 16 ~4.0×10 17 pieces cm -3 The reason why it is preferable that the range is within this range is that the lamellar ferrite is strengthened to increase the rail hardness and improve the wear resistance. By setting the particle size of the V-containing nitride in the ferrite to a particle size within the range of 0.5 to 4 nm, the effect of strengthening the lamellar ferrite can be obtained. In addition, the number density is preferably within 6.0×10 16 ~5.0×10 17 pieces cm -3 By setting the number density of the nitride particles containing V having a particle size of 0.5 to 4 nm in the ferrite, it is possible to obtain a further effect of strengthening the lamellar ferrite. 16 ~2.0×10 17 pieces cm -3 The range is.

[0033] (3) Steel chemical composition The component composition of the pearlitic rail according to the present embodiment may be limited for the following reasons. Note that "%" in the following description means "mass %" unless otherwise specified.

[0034] C: 0.65-1.20% C is an effective element for promoting pearlite transformation and ensuring wear resistance. If the C content is less than 0.65%, the minimum strength and wear resistance required for a rail cannot be maintained. If the C content exceeds 1.20%, a large amount of coarse pro-eutectoid cementite structure is generated, and wear resistance and ductility decrease. For this reason, the C content is limited to 0.65% to 1.20%. If the C content is 0.70% or more, 0.80% or more, or 0.90% or more, the wear resistance is further improved and the service life of the rail is further improved. The C content may be 1.10% or less, 1.00% or less, or 0.95% or less.

[0035] Silicon: 0.05 to 2.00% Si is an essential component as a deoxidizer. In addition, Si is an element that improves the hardness (strength) of the rail head by solid solution strengthening in the ferrite phase in the pearlite structure. Furthermore, Si is an element that suppresses the formation of proeutectoid cementite structure in hypereutectoid steel, suppresses the decrease in ductility, and suppresses the decrease in ductility. However, if the Si content is less than 0.05%, these effects cannot be fully expected. Furthermore, if the Si content exceeds 2.00%, many surface defects are generated during hot rolling, and weldability is reduced due to the generation of oxides. Furthermore, if the Si content exceeds 2.00%, hardenability increases significantly, and martensite structure that is harmful to the wear resistance and ductility of the rail is generated. For this reason, the Si content is limited to 0.05 to 2.00%. The Si content may be 0.10% or more, 0.20% or more, or 0.50% or more. The Si content may be 1.80% or less, 1.60% or less, or 1.20% or less.

[0036] Mn: 0.05 to 2.00% Mn is an element that improves hardenability and refines the pearlite lamellar spacing, thereby ensuring the hardness of the pearlite structure and improving the wear resistance. However, if the Mn content is less than 0.05%, the effect is small, making it difficult to ensure the wear resistance required for rails. Furthermore, if the Mn content exceeds 2.00%, the hardenability increases significantly and martensite structures that are harmful to wear resistance and ductility are easily formed. For this reason, the Mn content is limited to 0.05 to 2.00%. The Mn content may be 0.10% or more, 0.20% or more, or 0.50% or more. The Mn content may be 1.80% or less, 1.60% or less, or 1.20% or less.

[0037] Cr: 0.02~2.00% Cr increases the equilibrium transformation temperature, and as a result, ferrite and pearlite structures are refined, contributing to high hardness. Furthermore, Cr is an element that forms nitrides together with V and improves the hardness (strength) of pearlite structures by precipitation hardening. However, if the Cr content is less than 0.02%, the effect is small, and the effect of improving the hardness of rail steel is not observed. Furthermore, if the Cr content exceeds 2.00%, the hardenability increases, a martensite structure is formed, spalling damage originating from the martensite structure occurs at the head corners and top of the head, and surface damage resistance decreases. For this reason, the Cr content is limited to 0.02 to 2.00%. The Cr content may be 0.10% or more, 0.20% or more, or 0.50% or more. The Cr content may be 1.80% or less, 1.60% or less, or 1.20% or less.

[0038] V: 0.010~0.100% V is an important element in the steel according to the present disclosure. V suppresses and refines austenite grain growth during the manufacture of pearlite rails. By cooling the rail with refined austenite grains, fine pearlite is formed, improving the wear resistance of the pearlite rail. Furthermore, V may become a nucleus of nitrides by bonding with N atoms, forming nitride particles or clusters. When nitrides containing V are precipitated in ferrite, they are more preferable because they contribute to increasing the hardness of pearlite by suppressing the movement of dislocations.

[0039] If the V content is less than 0.010%, the effect cannot be expected sufficiently, and no increase in hardness or improvement in wear resistance is observed. On the other hand, if the V content is excessive, large nitride particles are precipitated on the cementite interface. The coarse nitrides on the cementite interface reduce the plastic deformability and cause a decrease in wear resistance. In addition, if the V content is excessive, V carbides are likely to be generated instead of V nitrides. Therefore, the upper limit of the V content is set to 0.100%. More preferably, the V content is in the range of 0.020 to 0.050%. The V content may be 0.015% or more, 0.020% or more, or 0.030% or more. The V content may be 0.090% or less, 0.080% or less, or 0.070% or less.

[0040] N: 0.0020~0.0200% N, together with V, becomes the nucleus of nitrides and forms nitride particles. Generally, about 0.0010% N is contained in steel as an impurity. However, by making the N content 0.0020% or more, it is preferable because nitride particles can be formed inside ferrite. On the other hand, if the N content exceeds 0.0200%, the nitride particles become large and are also formed on the cementite interface. This reduces the wear resistance. In addition, if the N content remains in high concentration as solid solution, it causes a reduction in ductility itself. Therefore, the N content is limited to 0.0020 to 0.0200%. The N content may be 0.0025% or more, 0.0030% or more, or 0.0050% or more. The N content may be 0.0180% or less, 0.0150% or less, or 0.0100% or less.

[0041] P:0.025% or less P is an element that deteriorates the ductility of rail steel. If the P content exceeds 0.025%, the effect cannot be ignored. Therefore, the P content is set to 0.025% or less. The P content may be set to 0.024% or less, 0.023% or less, or 0.022% or less. The lower limit of the P content is not particularly limited and may be 0%. On the other hand, from the viewpoint of reducing refining costs, the P content may be set to 0.010% or more, 0.011% or more, or 0.012% or more.

[0042] S: 0.025% or less S is an element that exists in steel mainly in the form of inclusions (MnS, etc.) and causes embrittlement of steel. In particular, when the S content exceeds 0.025%, the adverse effect on embrittlement cannot be ignored. Therefore, the S content is set to 0.025% or less. The S content may be 0.024% or less, 0.023% or less, or 0.022% or less. The lower limit of the S content is not particularly limited and may be 0%. On the other hand, from the viewpoint of reducing refining costs, the S content may be set to 0.008% or more, 0.009% or more, or 0.010% or more.

[0043] O: 0.0040% or less O is an impurity. There is no lower limit for the O content, but it may be 0.0001% from the viewpoint of production costs. On the other hand, if the O content is excessive, coarse oxides are generated, causing a decrease in the ductility and toughness of the steel. The O content is preferably 0.0030% or less, and more preferably 0.0020% or less.

[0044] Nb: 0% or more and less than 0.005% Ti: 0% or more and less than 0.005% Mo: 0 to 0.100% In addition, the rail manufactured with the above-mentioned composition may contain one or more of Nb, Ti, and Mo to refine the pearlite structure. Nb, Ti, and Mo are elements that are effective in preventing softening and embrittlement of the heat-affected zone of a welded joint by forming carbonitrides in a relatively high temperature range in the heat-affected zone reheated to a temperature range below the Ac1 point. In particular, Mo is an element that, in addition to forming carbonitrides, increases the equilibrium transformation temperature, like Cr, and as a result, refines the ferrite structure and pearlite structure, contributing to high hardness, and at the same time strengthens the cementite phase and improves the hardness (strength) of the pearlite structure. However, these elements are elements that tend to form large nitrides, and N is unnecessarily consumed. Therefore, Nb is preferably less than 0.0050%. Ti is preferably less than 0.0050%. Mo is preferably 0.100% or less. Mo is more preferably 0.005% or less. Nb, Ti, and Mo may each be 0.0040% or less, 0.0035% or less, or 0.0030% or less. It is not essential that Nb, Ti, and Mo are contained in the rail according to the present embodiment. Therefore, Nb, Ti, and Mo may each be 0%.

[0045] Furthermore, rails manufactured with the above-mentioned composition may contain the elements B, Co, Ni, Mg, Ca, Al and Cu as necessary for the purposes of refining the pearlite structure, increasing strength, improving ductility, preventing softening of the welded heat affected zone, controlling the cross-sectional hardness distribution inside the rail head, etc. However, these elements do not have to be contained in pearlite rails. The lower limit of each of the contents of B, Co, Ni, Mg, Ca, Al and Cu is 0%.

[0046] B: 0~0.0050% B is iron boride (Fe 23B is an element that forms B (CB)6) and reduces the cooling rate dependency of the pearlite transformation temperature by promoting the pearlite transformation, imparts a more uniform hardness distribution to the rail from the head surface to the inside, and extends the life of the rail. By making the B content 0.0001% or more, the effect can be fully exerted and the hardness distribution of the rail head can be improved. Furthermore, by making the B content 0.0050% or less, the formation of coarse iron borocarbides can be suppressed and ductility and toughness can be improved. For this reason, the B content may be 0.0001 to 0.0050%. The B content may be 0.0002% or more, 0.0003% or more, or 0.0005% or more. The B content may be 0.0040% or less, 0.0020% or less, or 0.0010% or less.

[0047] Co: 0 to 1.00% Co is an element that hardly acts on solid solution strengthening, but further refines the fine ferrite structure formed by contact with the wheel on the wear surface of the rail head, thereby improving wear resistance. When the Co content is 0.01% or more, the lamellar structure and ferrite grain size are refined, and the effect of improving wear resistance is exhibited. When the Co content is 2.00% or less, the ductility of the pearlite structure can be improved. When the Co content is 1.00% or less, the alloy cost can be suppressed and the economy can be improved. For this reason, the Co content may be limited to 0.01 to 1.00%. The Co content may be 0.02% or more, 0.05% or more, or 0.10% or more. The Co content may be 0.80% or less, 0.50% or less, or 0.10% or less.

[0048] Ni: 0 to 1.00% Ni improves the ductility in the pearlite structure and suppresses the decrease in ductility due to Co. At the same time, Ni is an element that hardens (strengthens) the rail by solid solution strengthening. If the Ni content is 0.01% or more, the effect can be sufficiently obtained. If the Ni content is 1.00% or less, the ductility of the ferrite phase in the pearlite structure can be increased, and the wear resistance of the pearlite structure can be increased. For this reason, the Ni content may be 0.01 to 1.00%. The Ni content may be 0.02% or more, 0.05% or more, or 0.08% or more. The Ni content may be 0.80% or less, 0.50% or less, or 0.10% or less.

[0049] Magnesium: 0 to 0.0200% Mg is an effective element for forming fine oxides by combining with O or S and Al, suppressing grain growth during reheating during rail rolling, refining austenite grains, and improving the ductility of ferrite and pearlite structures. Furthermore, MgO and MgS formed from Mg finely disperse MnS, forming a thin Mn layer around MnS, and contributing to the generation of ferrite and pearlite transformation. As a result, mainly the pearlite block size is refined. Therefore, Mg is an effective element for improving the ductility of pearlite structures. When the Mg content is 0.0005% or more, the effect can be sufficiently obtained. Furthermore, when the Mg content is 0.0200% or less, the generation of coarse Mg oxides can be suppressed, the toughness of the rail can be increased, and fatigue damage originating from coarse precipitates can be suppressed. For this reason, the Mg content may be limited to 0.0005 to 0.0200%. The Mg content may be set to 0.0008% or more, 0.0010% or more, or 0.0012% or more. The Mg content may be set to 0.0180% or less, 0.0100% or less, or 0.0030% or less.

[0050] Ca: 0 to 0.0200% Ca is an element that has a strong bond with S and forms CaS (sulfide). This CaS finely disperses MnS, relieves stress concentration, and improves the internal fatigue damage resistance of the rail. When the Ca content is 0.0005% or more, the effect can be sufficiently obtained. When the Ca content is 0.0200% or less, the generation of coarse Ca oxides can be suppressed. In the coarse Ca oxides, stress concentration that causes fatigue cracks is likely to occur. However, by suppressing the generation of coarse Ca oxides, the generation of fatigue cracks can be suppressed and the internal fatigue damage resistance can be improved. Therefore, the Ca content may be limited to 0.0005 to 0.0200%. The Ca content may be 0.0008% or more, 0.0010% or more, or 0.0012% or more. The Ca content may be 0.0180% or less, 0.0150% or less, or 0.0100% or less.

[0051] Al: 0 to 1.000% Al has a deoxidizing effect. In addition, Al is an element that shifts the eutectoid transformation temperature to the high temperature side, and contributes to the hardening (strength) of the pearlite structure. When the Al content is 0.025% or more, the effect can be sufficiently obtained. When the Al content is 1.000% or less, Al can be easily dissolved in steel, the number of coarse alumina-based inclusions can be reduced, the toughness of the rail can be improved, and fatigue damage caused by coarse precipitates can be prevented. Furthermore, when the Al content is 1.000% or less, oxides can be prevented from being generated in the welded portion, and weldability can be significantly improved. Therefore, the Al content may be limited to 0.025 to 1.000%. The Al content may be more than 0%, 0.028% or more, 0.030% or more, or 0.035% or more. The Al content may be 0.900% or less, 0.600% or less, or 0.400% or less.

[0052] Cu: 0-1.00% Cu is an element that dissolves or precipitates in ferrite and pearlite structures, and improves the hardness (strength) of the pearlite structure by solid solution strengthening or precipitation strengthening. Cu precipitate particles are soft, so they do not adversely affect wear resistance when precipitated in the ferrite phase. However, when the Cu content is high, the amount of Cu in solid solution also increases, and Cu reduces the wear resistance of the rail. On the other hand, from the viewpoint of recycling scrap steel, there is a high possibility that the rail contains Cu. Furthermore, Cu may be intentionally contained in the rail from the viewpoint of use as a solid solution strengthening element or surface damage resistance. In this sense, the Cu content may be 1.00% or less. The Cu content may be more than 0%, 0.01% or more, 0.05% or more, or 0.010% or more. It may be 0.20% or less, 0.10% or less, or 0.05% or less.

[0053] REM: 0~0.0500% REM is a deoxidizing and desulfurizing element, and when contained, it forms REM oxysulfide (REM2O2S) which becomes the nucleus of Mn sulfide-based inclusions. This oxysulfide (REM2O2S) has a high melting point. Therefore, oxysulfide suppresses the elongation of Mn sulfide-based inclusions after rolling. As a result, the inclusion of REM finely disperses MnS, relieves stress concentration, and improves the internal fatigue damage resistance of the rail. When the REM content is 0.0005% or more, the nucleus of MnS-based sulfides is sufficiently formed, and the above-mentioned effects are obtained. On the other hand, when the REM content is 0.0500% or less, the excessive formation of hard REM oxysulfide (REM2O2S) can be suppressed. In this case, the formation of fatigue cracks due to stress concentration is suppressed, and the internal fatigue damage resistance is further improved. For this reason, when REM is contained in a rail, the REM content is preferably 0.0005 to 0.0500%. More preferably, the lower limit of the REM content is 0.0010%, 0.0012%, or 0.0015%. More preferably, the upper limit of the REM content is 0.0400%, 0.0300%, or 0.0100%.

[0054] Here, REM refers to the rare earth metals of the group consisting of Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. The REM content is the total content of the rare earth metal elements. As long as the total content is within the above range, the same effect can be obtained whether the rail contains one type of rare earth metal element or two or more types.

[0055] Zr: 0 to 0.0200% Zr combines with O to form ZrO2-based inclusions. These ZrO2 inclusions have good lattice matching with γ-Fe. Therefore, ZrO2-based inclusions become solidification nuclei of high carbon rail steel in which γ-Fe is the solidification primary crystal, increase the equiaxed crystallization rate of the solidification structure, and refine the solidification structure. This finely disperses MnS, relieves stress concentration, and improves the internal fatigue damage resistance of the rail. Furthermore, Zr suppresses the formation of a segregation zone in the center of the cast slab, thereby suppressing the formation of martensite structures in the segregation parts of the rail. When the Zr content is 0.0001% or more, a sufficient number of ZrO2-based inclusions are formed to act as solidification nuclei. On the other hand, when the Zr content is 0.0200% or less, the formation of a large amount of coarse Zr-based inclusions is suppressed, fatigue cracks due to stress concentration are prevented, and the internal fatigue damage resistance of the rail can be further improved. Therefore, when Zr is contained, the Zr content is preferably 0.0001 to 0.0200%. The more preferable lower limit of the Zr content is 0.0005%, 0.0010%, or 0.0012%. The more preferable upper limit of the Zr content is 0.0100%, 0.0050%, or 0.0020%.

[0056] The balance of the chemical components of rail steel is mainly Fe. In addition to the above components, rail steel also contains impurities.

[0057] (4) Area ratio of pearlite structure The structure of the pearlitic rail according to the present embodiment in the range from the head outer surface to a depth of 25 mm (head surface portion 3a) is mainly pearlite structure. However, the structure in the range from the head outer surface to a depth of 25 mm may contain trace amounts of pro-eutectoid ferrite structure, pro-eutectoid cementite structure, bainite structure, or martensite structure of 5% or less in area ratio. However, even if these structures are mixed, it does not have a significant effect on the wear resistance and ductility of the rail head. Therefore, the structure in the range from the head outer surface to a depth of 25 mm of the pearlitic rail may contain trace amounts of pro-eutectoid ferrite structure, pro-eutectoid cementite structure, bainite structure, or martensite structure of 5% or less. In other words, it is sufficient that the structure in the range from the head outer surface to a depth of 25 mm of the pearlitic rail according to the present embodiment is 95% or more of pearlite structure. In order to ensure sufficient wear resistance and ductility, it is desirable to make the said range 98% or more of pearlite structure.

[0058] The meaning of the term "head outer surface" and other shapes of pearlite rails are explained below. The head 3 refers to the part above the part that is narrowed in the height direction center when the pearlite rail is viewed in cross section as shown in FIG. 3. The head 3 has a top 31 and head corners 32 located at both ends of the top 31. One of the head corners 32 is a gauge corner (GC) part that mainly comes into contact with the wheel. The head outer surface refers to the surface of the head 3 that faces upward when the rail is upright, combined with the surface of the top 31 and the head corners 32. The positional relationship between the top 31 and the head corners 32 is such that the top 31 is located almost in the center of the width direction of the rail head, and the head corners 32 are located on both sides of the top 31.

[0059] The area extending from the surface (head outer surface) of the head corners 32 and the head top 31 to a depth of 25 mm is called the head surface portion (3a, shaded area). As shown in Fig. 6, in order to improve the wear resistance and internal fatigue damage resistance of a rail, it is necessary for the head surface portion 3a extending from the surface (head outer surface) of the head corners 32 and the head top 31 to a depth of 25 mm to have a metal structure containing pearlite structure with a predetermined hardness (a metal structure containing pearlite structure at an area ratio of 95% or more).

[0060] (5) Hardness at a depth of 25 mm from the surface of the rail head portion 31 The reason for limiting the hardness at a position 25 mm deep from the surface of the rail top 31 to at least 350 Hv will be explained. In the present composition range, if the hardness at a position 25 mm deep from the surface of the rail top 31 is less than 350 Hv, flaking damage due to plastic deformation will occur on the rolling surface of the rail top 31. In addition, when pearlitic rails are used in heavy-duty railways, if the hardness at a position 25 mm deep from the surface of the rail top 31 is less than 350 Hv, it will be difficult to ensure wear resistance, and the service life of the rail will be reduced. For this reason, the hardness at a position 25 mm deep from the surface of the rail top 31 is limited to at least 350 Hv. The hardness at a position 25 mm deep from the surface of the rail top 31 may be 360 ​​HV or more, 380 HV or more, or 400 HV or more. Generally, the higher the hardness, the better the wear resistance. Therefore, the upper limit of the hardness at that position is not particularly specified, but may be, for example, 600 HV or less, 550 HV or less, or 500 HV or less.

[0061] (Manufacturing method) Rail steel having the above-mentioned chemical composition is produced by melting in a commonly used melting furnace such as a converter or electric furnace, and the molten steel is then produced into rails through the ingot-making and blooming method or the continuous casting method, and further through hot rolling.

[0062] An example of a preferred method for manufacturing a rail according to the present disclosure will be described. According to this manufacturing method, the number density of nitride particles with a diameter of 4 nm or more on the cementite interface is 1.0×10 10 pieces cm -2The hardness of the top portion is at least 350 Hv, and preferably, the number density of nitride particles having a particle size of 0.5 to 4 nm in the ferrite is 4.0 × 10 16 pieces cm -3 A pearlitic rail having the above structure can be obtained. However, the example of the manufacturing method described below does not limit the manufacturing method of the pearlitic rail according to the embodiment described above.

[0063] The number density of nitride precipitates with a size of 4 nm or more on the cementite interface in ferrite was set to 1.0×10 10 pieces cm -2 To keep the concentration of V in the ferrite at the interface below 100%, it is necessary to suppress the formation of nitrides on the cementite interface. Nitrides are likely to precipitate in areas of the ferrite after pearlite transformation where solute V is present at a high concentration. Since the nuclei of nitrides are VN, in order to suppress the precipitation of nitrides on the cementite interface, V is distributed from the cementite interface to the inner side of the cementite during pearlite transformation. This reduces the solute V concentration in the ferrite near the interface.

[0064] One example of a means for distributing V to the inner side of cementite is the optimization of cooling conditions. V has a small distribution coefficient at high temperatures and a slow diffusion at low temperatures, so it is difficult to distribute V to the inner side of cementite. Therefore, a temperature intermediate between these is preferable, and it is necessary to search for an optimal cooling rate according to the steel composition. In the manufacture of pearlitic rails, it is preferable to realize optimal temperature control.

[0065] In addition, 4.0×10 nitride particles with a particle size of 0.5–4 nm were added to the ferrite. 16 pieces cm -3 In order to achieve this, it is preferable to leave a sufficient amount of solute V in the center of the lamellar ferrite immediately after pearlite transformation. For this purpose, it is necessary to appropriately prevent the lamellar ferrite width from being too narrow and to optimize the cooling rate so that V is not excessively distributed to the cementite.

[0066] There is no particular upper limit for the heating temperature, but if the temperature is too high, a liquid phase appears and the austenite phase becomes unstable. Therefore, the temperature is practically limited to 1350°C. The lower limit for the heating temperature is preferably a high temperature of 1180°C or higher, since nitrides such as VN must be dissolved once.

[0067] In order to completely transform austenite into pearlite, the rail head immediately after rolling is set to a temperature range of Ar1 point or higher. When a rolled rail is cooled and then reheated to manufacture the rail, the reheated rail head is set to a temperature of Ac1 point +30°C or higher. Finish rolling is preferably performed at 900 to 950°C.

[0068] A rail immediately after rolling, or a rail that has been cooled and reheated after rolling, is preferably started to be cooled in the temperature range of 850 to 900° C. The time when cooling starts refers to the time when spraying of a coolant onto the rail starts. That is, it is preferable to start spraying of a coolant onto the rail head when the temperature of the rail head is in the temperature range of 850 to 900° C.

[0069] The cooling end temperature is preferably 790 to 820°C. The cooling end temperature refers to the point in time when the spraying of the coolant onto the rail is terminated. In other words, it is preferable to terminate the spraying of the coolant onto the rail head when the rail head is in the temperature range of 790 to 820°C.

[0070] The cooling rate is preferably 20 to 50°C / s. The cooling rate is the difference between the cooling start temperature (the temperature of the rail head when the spraying of the coolant begins) and the cooling end temperature (the temperature of the rail head when the spraying of the coolant ends) divided by the time the coolant is sprayed. The temperature of the rail head is measured by a radiation thermometer. The temperature is measured at the outer surface of the rail head.

[0071] By rapidly cooling the rail head under the above conditions, the grain growth of austenite is suppressed. If the cooling rate immediately after hot rolling is too high, the precipitation of carbonitrides on the high temperature side may be completely suppressed, and the driving force for the precipitation of nitrides at the cementite interface after pearlite transformation may increase. In this case, nitrides containing V tend to precipitate at the cementite interface. In addition, it is technically difficult to achieve a cooling rate of more than 50°C / s. At a cooling rate of less than 20°C / s, the effect of suppressing grain growth is small.

[0072] Following rapid cooling using a refrigerant, the material is slowly cooled at 2-5°C / s to 740-780°C, which is the temperature range immediately before the start of pearlite transformation (pre-controlled cooling). The start of pre-controlled cooling refers to the end of the above-mentioned coolant spraying. The end of pre-controlled cooling refers to the start of controlled cooling, which will be described later. The cooling rate in pre-controlled cooling is the difference between the rail head temperature at the start of pre-controlled cooling and the rail head temperature at the end of pre-controlled cooling, divided by the time required for pre-controlled cooling. The pre-controlled cooling shifts the pearlite transformation temperature slightly to the higher temperature side.

[0073] Following the above-mentioned slow cooling, the rail head is subjected to controlled cooling from the austenite temperature range to preferably 600 to 480°C at a cooling rate of preferably 5 to 12°C / s. That is, the end temperature of the controlled cooling is in the range of 600 to 480°C. Preferably, the end temperature of the controlled cooling is 580 to 480°C. This results in a complete pearlite structure. The start time of the controlled cooling is the time when the spraying of the coolant is started. The end time of the controlled cooling is the time when the spraying of the coolant is ended. The cooling rate in the controlled cooling is the value obtained by dividing the difference between the rail head temperature at the start time of the controlled cooling and the rail head temperature at the end time by the time required for the controlled cooling.

[0074] If the cooling rate of the controlled cooling is too high, the transformation temperature drops significantly. In this case, the distribution of V solid solution atoms during pearlite transformation does not occur sufficiently, and the V solid solution concentration in ferrite near the cementite interface does not decrease. Then, large nitrides tend to form on the cementite interface after pearlite transformation. If the cooling rate is too low or the end temperature is too high, the pearlite transformation proceeds at a higher temperature, resulting in coarse pearlite and less hardening due to lamellar refinement.

[0075] In reality, the precipitation driving force varies depending on the V, Cr and N contents, so the correspondence with the preferred manufacturing method is not simple and varies. If the V, Cr and N contents are within the ranges of this embodiment, the precipitation and enlargement of nitrides on the cementite interface can be suppressed by applying the above manufacturing conditions. Regarding the method of controlled cooling, for example, a refrigerant medium consisting of air or air mainly with mist or the like added, or a combination of these, can be used to obtain a predetermined cooling rate.

[0076] The manufacturing method described here is an example and does not limit the pearlite rail having the structure characteristics described in the claims. Pearlite rails having a similar structure obtained by other manufacturing methods also belong to the pearlite rail according to this embodiment. EXAMPLES

[0077] Next, an embodiment of the present disclosure will be described. However, the conditions in the embodiment are merely an example of conditions adopted to confirm the feasibility and effects of the present disclosure. The present disclosure is not limited to this example of conditions. Various conditions may be adopted in the present disclosure as long as the purpose is achieved without departing from the gist of the disclosure.

[0078] Tables 1A and 1B show the chemical compositions of the test rail steels. Tables 2A and 2B show the materials and manufacturing conditions of the test rail steels (Test Nos. 1 to 28) made of any of the steel types A to P disclosed in Tables 1A and 1B. Tables 3A and 3B show the state of precipitates in the ferrite phase. Tables 4A and 4B show the rail characteristics and the results of the wear test. As the manufacturing conditions, the cooling rate in each temperature range is shown. As the rail characteristics, the head hardness (Hv) (test load 98N) and the total elongation in the tensile test are shown. As the wear test, the wear amount (g) in the wear test of 700,000 times is shown. The balance of the chemical compositions listed in Tables 1A and 1B is iron and impurities. In Tables 1A and 1B, the symbol "-" in the column of the content of an element means that the element with that symbol is not intentionally added to the pearlite rail, and "<0.005" in the column of the content of an element in Tables 1A and 1B means less than 0.005 mass%.

[0079] The manufacturing conditions not listed in the table are as follows. After the components of these steel rails were adjusted in a converter, the steel billets for rail rolling, which were cast by continuous casting, were heated at a heating temperature of 1250°C for at least one hour. After holding at the temperature, hot rolling was performed with an interval between passes of 11 s. Finish rolling was performed at 910°C with a reduction in area of ​​10% per pass.

[0080] The rail was rapidly cooled from 900°C to 800°C at a cooling rate of 20-50°C / s from the hot rolling finish temperature by water cooling or the like, then slowly cooled to 760°C at a cooling rate of 2-10°C / s, and subsequently controlled-cooled at a cooling rate of 4-15°C / s until the rail head temperature reached 610-450°C. The characteristics of this rail sample were evaluated by the following methods.

[0081] The wear of the rail head was evaluated by a Nishihara type wear test under the following test conditions: Testing machine: Nishihara type abrasion testing machine - Test piece shape: Disc-shaped test piece (outer diameter: 30 mm, thickness: 8 mm) Test piece collection location: 5mm below the top surface of the rail Test load: 684N (contact pressure 640MPa) Slip rate: 20% ·Mating material: Pearlite steel (360Hv) Atmosphere: Air Cooling: Forced cooling by compressed air (flow rate: 100Nl / min) Number of repetitions: 700,000 The amount of wear was determined as the loss in mass of the test piece after the test. When the amount of wear was less than 1.00 g, the wear resistance was deemed good. When the amount of wear was less than 0.80 g, the wear resistance was deemed even better.

[0082] Furthermore, test pieces were cut out from the rail head and the total elongation was estimated from tensile tests.

[0083] Testing machine: Universal small tensile testing machine ·Test piece shape: JIS No. 4 similar Parallel section length: 30mm ·Parallel diameter: 6mm Distance between elongation measurement points: 25mm Test piece collection location: 5mm below the top surface of the rail Pulling speed: 10mm / min Test temperature: Room temperature The tensile test was carried out in accordance with JIS Z 2241:2011. A total elongation value of 10.0% or more was considered good.

[0084] The hardness of the top of the head was determined by Vickers hardness measurement using a load of 1 kg. The location was 25 mm below the surface of the top of the head. Since there was some variability, the average value of the measurement results at five points is listed in the table. A value of 350Hv or more was considered good.

[0085] The pearlite fraction was determined by nital etching of the polished sample surface. When the area ratio of the second phase other than pearlite phase was more than 5%, the main second phase was listed in the table. The measurement position of the pearlite fraction was within a range of 25 mm depth from the head outer surface. Specifically, samples were cut from the cross section of each rail head, each sample was diamond polished, etched with 3% nital, and then measured by observing the structure using an optical microscope (200x). In the structure observation at 200x magnification, the white parts are pro-eutectoid ferrite. Pro-eutectoid cementite can be identified as different contrasts along the grain boundaries. Martensite and bainite can be identified from the lath structure. The other structures are massive pearlite, and are identified from the different contrasts depending on the lamellar direction. If the structure is unknown, the pearlite lamellar structure can be identified by high-magnification observation using a scanning electron microscope (SEM). The measurement fields were 10 arbitrary fields at a depth of 2 mm from the head outer surface, and 10 arbitrary fields at a depth of 25 mm from the head outer surface. The average value of the area ratio of pearlite structure in 10 arbitrary fields at a depth of 2 mm from the head outer surface was defined as the "surface pearlite ratio," and the average value of the area ratio of pearlite structure in 10 arbitrary fields at a depth of 25 mm from the head outer surface was defined as the "25 mm position pearlite ratio." A rail in which both were 95 area % or more was determined to be a rail in which the structure in the range from the head outer surface to a depth of 25 mm contained 95% or more pearlite structure by area ratio.

[0086] The precipitates in the pearlite structure at a depth of 25 mm from the head outer surface were investigated by 3D atom probe observation using a CAMECA LEAP4000XHR. A needle sample with a curvature radius of 30 to 80 nm was fabricated from the pearlite structure at a depth of 25 mm from the head outer surface of the sample pearlite rail by focused ion beam (FIB) processing. Measurements of 20 million atoms were performed multiple times using the 3D atom probe. From this data, a 3D elemental map can be obtained, for example, using IVAS software, a 3D construction software. V is the mass-to-charge ratio, which is V with a peak appearing at 25.5 Da. 2+ ion and VN with a peak at 32.5 Da2+ ions are detected. 2+ The ions are composed of V and N, and therefore indicate the presence of nitride particles containing V. Areas where C is concentrated at 20 at% or more become cementite lamellae. There are two types of precipitates: particles that exist on the cementite interface, and particles that are distributed within ferrite grains away from the cementite interface (see Figure 1).

[0087] An example of a 3D elemental map of a V-doped rail is shown in Figures 4A-4D. These are atomic maps of Fe, C, and V in the same rectangular region with a height of 77 nm, a width of 78 mm, and a length of 232 nm. Each point in the map represents one atom. For V, V 2+ Ion map and VN 2+ The ion map and VN 2+ The ion is a pair of N and V, so VN 2+ The areas where the dots representing ions are concentrated correspond to nitride particles containing V. The C atomic map shows lamellar cementite and lamellar ferrite. In the figure, lamellar cementite is written as "cementite" and lamellar ferrite is written as "ferrite". VN 2+ In the map, fine nitride particles are observed in the ferrite, and the slightly larger particles enclosed in a square box marked with an X are nitride particles on the cementite interface.

[0088] 5A to 5D show the VN 2+ The three-dimensional elemental map of the square box region X set in the map is shown. This box has a cubic shape with each side of 10 nm. Figures 5A to 5D show atomic maps of C, V, Cr, and Mn. Here, the atomic map of V is VN 2+ and V 2+ 5A to 5D are a combination of the above. In the C atom map, the position of the interface between cementite and ferrite is indicated by a dashed line. It is shown that nitride particles containing V and Cr are in contact with cementite, that is, they are present on the cementite interface. Also, Figs. 5A to 5D show that C atoms are not included in the nitride particles.

[0089] The type, number density, and size of nitride particles on the cementite interface were estimated as follows. The number n of nitride particles in contact with the cementite interface in the element map was calculated, and this was used as the total surface area S nm 2 The number density of nitride particles per cementite interface area, n / Snm, is obtained by dividing by ―2 If lamellar cementite crosses the map, the area must be calculated by adding up both sides. Also, as shown in Tables 3A and 3B, the unit is cm -3 When converting to 14 Just multiply it by .

[0090] The type, number density, and size of nitride particles in ferrite were estimated as follows. For example, in the case of measuring 20 million atoms, the value was divided by the detection rate (~0.38) of the ion detector in the device, and the atomic density of Fe (~85 nm -3 ) is the measured volume (nm 3 ) This detection rate does not change depending on the number of atoms or the type of element, but is determined by the device. In order to obtain the number density in the ferrite phase, if the cementite phase is included in the measurement field of view, this volume must be excluded from the measurement volume V of the ferrite phase. f (nm 3 If n precipitates are observed in this measurement volume, the number density is n / V f nm ー3 As shown in Table 2A and Table 2B, the unit is cm -3 When converting to 21 Just multiply it by .

[0091] To improve accuracy, multiple measurements were taken across the cementite lamella. For example, if one precipitate was observed in a measurement of the volume equivalent to 30 million atoms in ferrite, the area of ​​about 1.0 × 10 15 pieces cm -3 In addition, if no precipitates were observed by such measurements, it was indicated as "-". Therefore, if no precipitates were observed, the number density was 1.0×10 15pieces cm -3 For example, if the area of ​​the cementite interface in the 3D element map is 100 nm × 50 nm × 2 = 10,000 nm 2 When one nitride particle is observed on the cementite interface, the average particle size is 1.0×10 10 pieces cm -2 In cases where such cementite was not observed even after multiple measurements, it is indicated as "-" in the table.

[0092] The composition of the precipitate particles was determined by determining the constituent elements and their atomic numbers of nitride particles using a particle analysis program such as the Maximum seperation method included in IVAS software, a 3D construction software made by CAMECA. It may also be determined by cutting a box directly on the 3D element map. The version of the IVAS software was 3.6.8. However, the software version does not affect the measurement results. The size of the precipitate particles was calculated as the equivalent sphere diameter as follows: The number of constituent atoms other than nitrogen was calculated using the above method. This is because the current atom probe cannot measure all nitrogen atoms correctly. Assuming a stoichiometric composition, in a NaCl-type crystal structure, the number of constituent atoms of the nitride particles, including nitrogen, is twice the number of constituent atoms other than nitrogen, such as V, Cr, Mn, etc. Furthermore, this value was divided by the ion detection rate of the atom probe (0.38 in this case) to find the actual number of constituent atoms N. Finally, assuming a sphere with diameter D, and the atomic density of the precipitate as a, D = (6N / πa) 1 / 3 The particle diameter D can be calculated from the above equation. Here, the atomic density is a = 113 nm -3 The number density of V-containing nitride particles with a grain size of 4 nm or more on the cementite interface and the number density of nitride particles with a grain size of 0.5 to 4 nm in ferrite estimated using this method are shown in Tables 3A and 3B.

[0093] [Table 1A]

[0094] [Table 1B]

[0095] [Table 2A]

[0096] [Table 2B]

[0097] [Table 3A]

[0098] [Table 3B]

[0099] [Table 4A]

[0100] [Table 4B]

[0101] In test No. 1 (steel type A), the amount of C was insufficient. In test No. 1, pro-eutectoid ferrite was mixed into the structure in the range from the head outer surface to a depth of 25 mm, and the area ratio of pearlite structure was less than 95%. In test No. 1, the hardness at a position 25 mm deep from the surface of the top of the head was insufficient, and wear resistance was insufficient.

[0102] In test No. 2 (steel type B), the amount of N was insufficient. In test No. 2, the hardness at a depth of 25 mm from the surface of the top of the head was insufficient, and wear resistance was impaired.

[0103] In test No. 3 (steel type C), the amount of V was insufficient. In test No. 3, the hardness at a depth of 25 mm from the surface of the top of the head was insufficient, resulting in insufficient wear resistance.

[0104] In Test No. 11, the cooling rate in the accelerated cooling immediately after hot rolling was excessive. In Test No. 11, the number density of nitride particles present on the cementite interface became excessive, and the wear resistance was impaired.

[0105] In Test No. 12, the cooling rate in the controlled cooling was excessive. In Test No. 12, the number density of nitride particles present on the cementite interface became excessive, and the wear resistance and ductility were impaired.

[0106] In test No. 13, the cooling rate in the controlled cooling was excessive. In test No. 13, bainite was mixed into the structure in the range from the head outer surface to a depth of 25 mm, and the area ratio of pearlite structure was less than 95%. In test No. 13, the wear resistance was impaired.

[0107] In Test No. 14, the cooling rate in the controlled cooling was insufficient. In Test No. 14, the number density of nitride particles present on the cementite interface became excessive, and the wear resistance was impaired.

[0108] In test No. 15, the end temperature of the controlled cooling was too low. In test No. 15, bainite was mixed into the structure ranging from the head outer surface to a depth of 25 mm, and the area ratio of pearlite structure was less than 95%. In test No. 15, wear resistance and ductility were impaired.

[0109] In test No. 16, the end temperature of the controlled cooling was too high. In test No. 16, the number density of nitride particles present on the cementite interface became excessive, which impaired the wear resistance.

[0110] In test No. 17, the cooling rate in the accelerated cooling immediately after hot rolling was insufficient. In test No. 17, the number density of nitride particles present on the cementite interface became excessive, and ductility was impaired.

[0111] In test No. 18, the cooling rate in the cooling before controlled cooling was excessive. In test No. 18, the number density of nitride particles present on the cementite interface became excessive, and the wear resistance was impaired.

[0112] In Test No. 19, the cooling rate in the cooling before controlled cooling was insufficient. In Test No. 19, the number density of nitride particles present on the cementite interface became excessive, and the wear resistance was impaired.

[0113] Test No. 20 (steel type H) contained an excessive amount of N. In Test No. 20, the number density of nitride particles present on the cementite interface became excessive, and ductility was impaired.

[0114] In test No. 21 (steel type I), the amount of V was excessive. In test No. 21, the wear resistance was impaired.

[0115] In test No. 22 (steel type J), ​​the amount of C was excessive. In test No. 22, pro-eutectoid cementite was mixed into the structure in the range from the head outer surface to a depth of 25 mm, and the area ratio of pearlite structure was less than 95%. In test No. 22, wear resistance and ductility were impaired.

[0116] In test No. 23 (steel type K), the Si content was excessive. In test No. 24 (steel type L), the Mn content was excessive. In test No. 25 (steel type M), the Cr content and Mo content were excessive. In test Nos. 23 to 25, martensite was mixed into the structure in the range from the head outer surface to a depth of 25 mm, and the area ratio of the pearlite structure was less than 95%. In test Nos. 23 to 25, wear resistance and ductility were impaired.

[0117] In test No. 26 (steel type N), the Nb content was excessive. In test No. 26, the number density of nitride particles present on the cementite interface became excessive, and ductility and wear resistance were impaired.

[0118] In test No. 27 (steel type O), the Ti content was excessive. In test No. 27, the number density of nitride particles present on the cementite interface became excessive, and wear resistance was impaired.

[0119] In test No. 28 (steel type P), the Ti content was excessive. In test No. 28, the number density of nitride particles present on the cementite interface became excessive, and ductility and wear resistance were impaired.

[0120] On the other hand, in Test Nos. 4 to 10 and Test Nos. 29 to 36, in which the chemical components, hardness, pearlite area ratio, and state of nitrides on the cementite interface were all appropriate, both ductility and wear resistance were excellent. [Explanation of symbols]

[0121] 1 Pearlite structure 11 Cementite (lamellar cementite) 12 Ferrite (lamellar ferrite) 13 Cementite interface 21 Nitride particles present on the cementite interface 22 Nitride particles in ferrite, separated from the cementite interface 3 head 31 Top of the Head 32 Head corner 3a Head surface (area starting from the outer surface of the head to a depth of 25 mm)

Claims

1. In mass percent, C: 0.65-1.20%, Si: 0.05-2.00%, Mn: 0.05-2.00%, Cr: 0.02-2.00%, N: 0.0020-0.0200%, V: 0.010-0.100%, Nb: 0% or more and less than 0.005% Ti: 0% or more and less than 0.005% Mo: 0-0.100%, B: 0 to 0.0050%, Co: 0-1.00%, Ni: 0 to 1.00%, Mg: 0 to 0.0200%, Ca: 0-0.0200%, Cu: 0 to 1.00%, REM: 0 to 0.0500%, and Zr: 0-0.0200% P: 0.025% or less, S: 0.025% or less, Al: 0-1.000%, O: 0.0040% or less, and the balance being Fe and impurities, The structure in the range from the head outer surface to a depth of 25 mm contains a pearlite structure in an area ratio of 95% or more, The hardness at a depth of 25 mm from the surface of the top of the head is at least HV350; The number density per unit interface area of ​​V-containing nitride particles having a particle size of 4 nm or more present on the cementite interface of the pearlite structure at the position 25 mm deep from the surface of the top portion is 1.0 × 10 10 pieces cm -2 is less than A pearlite rail characterized by:

2. In the ferrite of the pearlite structure, nitride particles containing V having a particle size of 0.5 to 4 nm and separated from the cementite interface are present in a number density per unit volume of 4.0 × 10 16 ~4.0 x 10 17 pieces cm -3 exists in the range 2. The pearlitic rail according to claim 1 .

3. Further, in mass %, B: 0.0001 to 0.0050%, Co: 0.01 to 1.00%, Ni: 0.01-1.00%, Mg: 0.0005-0.0200%, Ca: 0.0005-0.0200%, Cu: more than 0% and less than 1.00% REM: 0.0005-0.0500% Zr: 0.0001-0.0200% Al: more than 0% and less than 1.000%, 3. The pearlite rail according to claim 1, further comprising at least one selected from the group consisting of:

Citation Information

Patent Citations

  • Pearlitic rail

    JP2002088449A

  • Manufacturing method for T-rail with high-strength foot

    JP2022514099A

  • Rail and method for manufacturing same

    WO2019189686A1

  • rail

    WO2020189232A1

  • Producing method for highly wear resistant and high toughness rail

    JP2001234238A